Close to threshold η′ meson production in proton-proton collisions at cosy-11 - Czerwiński E.; Moskal P.; Silarski M. (EPJ Web of Conferences, 2014)
We summarize results from measurements of excitation function for pp → ppη′ reaction performed at COSY-11 detector. The determined cross sections enabled an extraction of the scattering length of the η′-proton interaction in the vacuum.